2003
DOI: 10.1080/02687030344000067
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of writing: A functional magnetic resonance imaging study

Abstract: Plate 1. Surface-rendered projections of statistical maps reflecting activation during (1a) generative writing of words versus repetitive drawing of circles; (1b) generative writing of words versus writing letters of the alphabet; (1c) writing letters of the alphabet versus repetitive drawing of circles; (1d) generative writing of words versus generative subvocal naming of words. Display threshold set at T = 4.02 (uncorrected p < .001; extent threshold 50 voxels). Plate 2. Coronal and axial sections showing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 51 publications
(68 reference statements)
5
121
0
2
Order By: Relevance
“…For both modalities, there were modulatory effects involving inferior frontal gyrus, inferior parietal cortex and fusiform gyrus. This is broadly consistent with studies in adults that have reported activation in these regions in a variety of spelling tasks (Beeson et al, 2003;Booth et al, 2002;Katanoda et al, 2001;Menon and Desmond, 2001;Nakamura et al, 2000;Petrides et al, 1995;Sugihara et al, 2006;Sugishita et al, 1996;Tokunaga et al, 1999). None of these studies, however, found activation in superior temporal gyrus, whereas our study revealed reliable activation in and modulatory effects on connections with superior temporal gyrus in both visual and auditory modalities.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…For both modalities, there were modulatory effects involving inferior frontal gyrus, inferior parietal cortex and fusiform gyrus. This is broadly consistent with studies in adults that have reported activation in these regions in a variety of spelling tasks (Beeson et al, 2003;Booth et al, 2002;Katanoda et al, 2001;Menon and Desmond, 2001;Nakamura et al, 2000;Petrides et al, 1995;Sugihara et al, 2006;Sugishita et al, 1996;Tokunaga et al, 1999). None of these studies, however, found activation in superior temporal gyrus, whereas our study revealed reliable activation in and modulatory effects on connections with superior temporal gyrus in both visual and auditory modalities.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that brain regions implicated in phonological, and not semantic processing, were recruited for spelling (Poldrack et al, 1999). Our finding, showing the importance of dorsal inferior frontal gyrus in spelling, is consistent with several studies in adults reporting activation in BA 9/44 in spelling tasks (Booth et al, 2002;Katanoda et al, 2001;Nakamura et al, 2000;Tokunaga et al, 1999), although there is one inconsistent study showing activation in ventral inferior frontal gyrus (Beeson et al, 2003). In addition, our results of developmental increases in the modulatory effects into dorsal inferior frontal gyrus is consistent with studies using a similar auditory spelling task that have shown developmental increases in signal intensity in dorsal inferior frontal gyrus (BA 44/9) (Booth et al, 2003b(Booth et al, , 2004.…”
Section: Effective Connectivity From Primary Auditory Cortexsupporting
confidence: 81%
See 2 more Smart Citations
“…The phonological codes involved in spelling rely on a network of perisylvian cortical regions, including Broca's area, Wernicke's area, the supramarginal gyrus, and insula (Alexander et al, 1992;Fiez, 1997;Omura et al, 2004;Roeltgen et al, 1983). Orthographic knowledge of lexical representations for reading and spelling is thought to engage a critical region within temporo-occipital cortex (BA 37), sometimes referred to as the visual word form area (Beeson et al, 2003b;Cohen & Dehaene, 2004;Nakamura et al, 2002;Rapcsak & Beeson, 2004). Thus under normal circumstances, spelling engages both perisylvian and extrasylvian cortical regions.…”
Section: Introductionmentioning
confidence: 99%